Giving voice to older adults living with frailty and their family caregivers: engagement of older adults living with frailty in research, health care decision making, and in health policy. Issue 1 (December 2016) - Holroyd-Leduc, Jayna; Resin, Joyce; Ashley, Lisa; Barwich, Doris; Elliott, Jacobi; Huras, Paul; Légaré, France; Mahoney, Megan; Maybee, Alies; McNeil, Heather; Pullman, Daryl; Sawatzky, Richard; et al.
Plain English summary The paper discusses engaging older adults living with frailtyand their family caregivers. Frailty is a state that puts an individual at a higher risk for poor health outcomes and death. Understanding whether a person is frail is important because treatment and health care choices for someone living with frailty may be different from someone who is not (i.e., who is fit). In this review, we discuss strategies and hurdles for engaging older adults living with frailty across three settings: research, health and social care, and policy. We developed this review using published literature, expert opinion, and stakeholder input (including citizens). Engaging frail older individuals will be challenging because of their vulnerable health state - but it can be done. Points of consideration specific to engaging this vulnerable population include:In any setting, family caregivers (defined to include family, friends, and other social support systems) play an important role in engaging and empowering older adults living with frailty Engagement opportunities need to be flexible (e.g., location, time, type) Incentivizing engagement for researchers and citizens (financial and otherwise) may be necessary The education and training of citizens, health and social care providers, and researchers on engagement practices Patient-centered care approaches should consider the specific needs of individuals living with frailty including end-of-life care and advanced care planning Influencing policy can occur in many ways including participating at institutional, regional, provincial or national committees that relate to health and social care. Abstract Older adults are the fastest growing segment of Canada's population resulting in an increased number of individuals living with frailty. Although aging and frailty are not synonymous the proportion of those who are frail increases with age. Frailty is not defined by a single condition, but rather a health state characterized by an increased risk of physical, mental, or social decline, deterioration of health status, and death. Recognizing frailty is important because earlier detection allows for program implementation focused on prevention and management to reduce future hospitalization, improve outcomes, and enhance vitality and quality of life. Even though older adults living with frailty are significant users of health care resources, their input is under-represented in research, health care decision making, and health policy formulation. As such, engaging older adults living with frailty and their family caregivers is not only an ethical imperative, but their input is particularly important as health and social care systems evolve from single-illness focused to those that account for the complex and chronic needs that accompany frailty. In this review, we summarize existing literature on engaging older adults living with frailty and their family caregivers across three settings: research, health and social care, and policy. We discuss strategies and barriers to engagement, and ethical and cultural factors and implications. Although this review is mainly focused on Canada it is likely to be broadly applicable to many of the health systems in the developed world where aging and frailty pose important challenges.